P400Spatial relationship between atrial fibrillation drivers identified by dipole density mapping and left atrial fibrosis. (18th June 2020) - Ammar-Busch, S; Forkmann, M; Tose Costa Paiva, B; Mitlacher, M; Mahnkopf, C
Abstract: Background: Atrial fibrillation (AF) is a complex arrhythmia and several mechanisms that might coexist have been proposed. Recent technical advances opened the way to better mapping possibilities and might contribute to target more specific components of the AF substrate. Objective: The aim of this study was to evaluate a spatial correlation between AF drivers as determined by a novel non-contact unipolar high-resolution system and atrial fibrosis assessed by cardiac magnetic resonance imaging (MRI). Methods: Patients undergoing a first ablation procedure for persistent AF were included. Prior to ablation, a Late Gadolinium-Enhancement (LGE) MRI was performed to detect the fibrotic atrial tissue. The procedure was performed using a new non-contact unipolar high-resolution system allowing a 3D anatomy reconstruction with a continuous dipole density mapping. Three different wave front patterns were analyzed in the left atrium (LA): 1) focal activity (FA), 2) localized rotational activation (LRA) and 3) localized irregular activation (LIA). The spatial distribution of these AF drivers was analyzed prior to AF ablation. Results: A total of 49 patterns in 6 patients were identified, among them 22 FA, 14 LRA and 13 LIA. The posterior (n = 14), anterior wall (n = 13) and roof (n = 8) were identified as predominant driver sites. 31/49 (59%) drivers had a strong correlation with late enhancement in MRI. Most of the LIA, LRA and FA were embedded infibrotic areas (LIA 10/13 (77%); LRA 9/14 (64%) and FA 12/22 (54%). The postero-inferior LA showed the best correlation between drivers and fibrosis, the antero-septal LA the weakest one. Conclusion: There is a significant overlap between AF driver regions identified by dipole density mapping and atrial fibrosis assessed by MRI. Most of AF drivers are embedded in fibrotic areas, particularly in case of localized irregular activity and at the posterior LA.